Reforming of Energy Sector of Uzbekistan: Transition to Market and Increasing Generation - A.G. Saidkhodjaev; Kh.R. Nuriddinova; N. Toshpulatov; B.B. Kadraliev (Zien Journals, 2022)
By 2030, Uzbekistan will need to generate 2 times more electricity than today in order to meet the needs of the economy and the population, or, in other words, to ensure the country's energy security. To achieve this goal which was set by the leadership of the country, the Ministry of Energy of the Republic of Uzbekistan is gradually implementing large-scale projects and coordinating the processes of reforming the industry in order to transfer it to market relations.
Keywords: Reforming; energy sector; increasing generation; thermal energy